Brasileiros e brasileiras: a retórica presidencial brasileira, de Deodoro da Fonseca a Jair Bolsonaro - Milanez, Aline Andrea Zamboni (2024)
The speeches delivered by political leaders reflect not only their personal and party ideologies but also the historical contexts and challenges faced during their mandates. Although they have been addressed in various linguistic fields, such as in argumentation (Partington, 2003), persuasion (Milanez, 2019), and representations (Baker, 2006), there is still a gap in research regarding Brazilian political speeches from the perspective of Corpus Linguistics. This study opted for a methodological approach based on Multidimensional Analysis, considered the most suitable for analyzing a wide range of speeches. Hence, following Biber’s (1988), Berber Sardinha’s, Kauffmann’s and Acunzo’s (2012, 2014a, 2014b) functional multidimensional analysis models, a comprehensive study was conducted on the official speeches of Brazilian presidents from 1889 to 2022. A total of 8,400 speeches were collected and then tagged by the “Palavras” program (Bick, 2014). The resulting grammatical variables were counted, normalized and then input into the SAS statistical program for factor analysis. Four factors were extracted and interpreted, generating the dimensions of the Brazilian Corpus of Political Speeches (CBDP): Solemn and Protocol Speech vs. Involved Informational Speech; Conversational Expository Monologue; Argumentation and Positioning; Ceremonial Protocol. In addition to functional analysis, an additive analysis was performed to understand how political speeches fit into the multidimensional analysis of the Portuguese language (CBVR). Furthermore, the study identified the individual linguistic style of seven Brazilian presidents, using the same approach